Clinical Commissioning and Dosimetric Verification of the Raystation Treatment Planning System - Tuğrul, Taylan (East European Journal of Physics, 2021)
Background: The software used by treatment planning systems (TPS) plays an important role for treatments using radiation. The accuracy of the calculated dose in radiation treatments depends on the assumptions made by the TPS. In this study, we summarize our methods and results regarding clinical commissioning of the basic functions needed for photon therapy. Materials and Method: Measurements were obtained for the 6 and 15 MV photon energies obtained from the Siemens Artiste linear accelerator device. Important data such as percent deep dose, profile and output measurements were taken in the water phantom and transferred to the RayStation Treatment Planning System. Results: When the absolute dose values calculated by the RayStation TPS are compared with the water phantom data, the differences obtained are less than 3%. When the 2-dimensional quality control of asymmetrical areas and patients with IMRT plan was controlled by gamma analysis method, the gamma rate was more than 95%. Conclusion: One of the most important quality control tests is TPS acceptance tests, which must be performed before clinical use. In this study, in which we checked the basic dose measurement and patient planning, it was seen that the RayStation TPS can be used in patient treatment for clinical use. The doses calculated by the RayStation TPS were found to be reliable and within the expected accuracy range. These results are sufficient for the application of 3-dimensional conformal radiotherapy (3D-CRT) and IMRT technique.